PERSUASI DAN JANTURAN DALAM PERTUNJUKAN WAYANG PURWA - Herawati, Nanik (Prosiding Seminar Nasional dan Internasional HISKI, 2024)
This article describes the major power persuation in the wayang puppet show showed by dalang 'puppeteer'. It also shows the dalang's attitude in his janturan 'adoring song'. The janturan contains persuasive naration for the audience to be obidient toward the rule of the nation. And this requires creativity of the dalang. The theory that underlies this article is that persuasion is an invitation to someone with soft and convincing reason. The result od the discussion explains that wayang puppet show in general has two parts, they are talu 'the beginning part' and jejer 'the real show begins'. The talu is usually interesting. The music for talu is called ayak-ayak and sampak. Soon talu is followed by the first jejer. This is the sacral trilogy. At the beginning of the show, dalang performs the janturan to adore and praise the country. In this part the dalang persuades the audience to obey the rule. The persuasion in the first part is good time because the audience is still in fresh and sacral condition.